Integration protection system based on distance algorithm - JINGHAN,BO HE (2006)
The integrated protective system based on distance algorithm comprises: an interface unit, a redundant integrated protective unit, and the fiber communication network unit, wherein the integrated relay unit in transformer substation connects with wires and near substation and central protective control unit by CT and PT; for fault in I area, the protection can immediate tripping; when detecting fault in II area, the relay communicates with remote relay to determine continual operation or back. This invention can protect every line to cover whole network.